(untitled) (European Bison Conservation Newsletter, 2015)
In this paper are discussed the results of monitoring the level of helminth infections in various populations of European bison in current conditions of the region of Belarus In 2012–2014 the analysis of 398 coproscopy fecal samples of European bison was performed using the precipitation and flotation methods.